2011
DOI: 10.1111/j.1399-3062.2011.00699.x
|View full text |Cite
|
Sign up to set email alerts
|

Dengue virus infection in renal allograft recipients: a case series during 2010 outbreak

Abstract: Dengue virus infection is an emerging global threat caused by Arbovirus, a virus from Flaviridiae family, which is transmitted by mosquitoes, Aedes aegypti and Aedes albopictus. Renal transplant recipients who live in the endemic zones of dengue infection or who travel to an endemic zone could be at risk of this infection. Despite multiple epidemics and a high case fatality rate in the Southeast Asian region, only a few cases of dengue infection in renal transplant recipients have been reported. Here, we repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 13 publications
2
45
2
Order By: Relevance
“…The day biting Aedes egyptii mosquite borne dengue viral infection in KTRs could be life threatening especially if presenting with hemorrhagic manifestations or dengue shock syndrome [115]. Effective critical care with fluid resuscitation, blood transfusion support and conservative measures is the usual line of treatment.…”
Section: Denguementioning
confidence: 99%
“…The day biting Aedes egyptii mosquite borne dengue viral infection in KTRs could be life threatening especially if presenting with hemorrhagic manifestations or dengue shock syndrome [115]. Effective critical care with fluid resuscitation, blood transfusion support and conservative measures is the usual line of treatment.…”
Section: Denguementioning
confidence: 99%
“…A previous study reported three renal transplant recipients that died because of DSS, and they had received antithymocyte immunoglobulin as acute rejection prophylaxis. 3 In summary, dengue is an important infectious disease in endemic areas that can affect renal transplant recipients and its presentation seem to be similar to that seen in immunocompetent patients. There is no specific therapy or vaccine for dengue.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] Kidney transplant patients that live in endemic zones or who travel to an endemic zone might be affected by this disease, similar to the general population. Previous studies suggest that dengue infection is mild in renal transplant recipients, with good recovery, and that the disease does not affect allograft function.…”
mentioning
confidence: 99%
“…Four case series of dengue infection in renal allograft recipients are available in the literature with the largest series consisting of 27 patients of which one patient developed DHF and died 11. In the case series from India, three out of eight patients developed DHF and expired 12. Four patients out of 10 dengue cases developed DHF in the series from Brazil but none of them expired 13.…”
Section: Discussionmentioning
confidence: 99%